The Governance of Canadian Domestic Multi-Sport Events: A Focus on Stakeholder Coordination and Knowledge Management - Schenk, Jessica Lin (Université d'Ottawa / University of Ottawa, 2015)
This dissertation’s purpose was to explore the governance of two domestic multi-sport events—2012 Ontario Summer Games and 2013 Canada Games—regarding how stakeholder coordination and knowledge management occurred. Case studies were built using content and social network analyses of 27 interviews and 476 document pages. In both events, the organizing committee staff and sport organizations were the most salient stakeholders, being therefore seen as the focal actors within the event network regarding coordination, initiating communication, building trust, and improving relationships. For the provincial event specifically, findings suggested the organizing committee should exist within an enduring organization in order to maximize resources (e.g., financial, human, etc.), build long-term coordination mechanisms, and enhance knowledge management capacities. Knowledge transfer appeared to occur at both levels, to varying degrees of sophistication. The knowledge management processes at each event stressed the importance of people and of tacit knowledge. Implications for researchers and managers provided.
Keywords: knowledge management; stakeholder coordination; domestic events; events; sport events; knowledge transfer